Project Sun Gazers - O. N. Mikhalyaev; M. E. Sapraliev; G. A. Mankaeva; T. V. Velegurin; L. N. Kharldaev (Современная наука и инновации, 2024)
An actual task of modern solar physics is the prediction of geoeffective phenomena, which include the fast solar wind, flares, and coronal plasma ejections that cause perturbations of the geomagnetic field in near-Earth space. Some of these disturbances are well known as magnetic storms. The goal of the Sun Gazers project is to create a database, three-dimensional visualization and forecast of the events described above. This database will allow us to match initial and boundary conditions for MHD-modeling. Visualization is necessary for visual comparison and analysis of the events of the above database.